2013
DOI: 10.1186/2050-7771-1-33
|View full text |Cite
|
Sign up to set email alerts
|

Statins inhibit proliferation and cytotoxicity of a human leukemic natural killer cell line

Abstract: BackgroundNatural killer cells comprise the body’s first line of defense against virus-infected cells. As is true of all lymphocytes, natural killer cell malignancies can develop, however natural killer cell leukemias can be very difficult to treat due to their intrinsic resistance to chemotherapeutic agents. With the recent understanding that statin drugs may have anti-cancer properties, our investigations have focused on the ability of statins to inhibit the growth and cytotoxicity of the YT-INDY natural kil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
19
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 20 publications
3
19
1
1
Order By: Relevance
“…The second correlated expression profile with statin use was a signature of improved prognosis among pediatric acute myeloid leukemia patients (AML). In tumor cell lines, statins were shown to inhibit the growth of acute myeloid leukemia cells [ 51 ], to synergistically increase the killing of the human erythroleukemia cell line K562 by the chemotherapeutic agent cytosine arabinoside [ 52 ], and to inhibit the proliferation and cytotoxicity of a human leukemic natural killer cell line [ 53 ]. The third correlated signature with statin use was a signature of Parkinson’s disease (PD) patients when compared with healthy or neurodegenerative disease controls[ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The second correlated expression profile with statin use was a signature of improved prognosis among pediatric acute myeloid leukemia patients (AML). In tumor cell lines, statins were shown to inhibit the growth of acute myeloid leukemia cells [ 51 ], to synergistically increase the killing of the human erythroleukemia cell line K562 by the chemotherapeutic agent cytosine arabinoside [ 52 ], and to inhibit the proliferation and cytotoxicity of a human leukemic natural killer cell line [ 53 ]. The third correlated signature with statin use was a signature of Parkinson’s disease (PD) patients when compared with healthy or neurodegenerative disease controls[ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Statins are inhibitors of 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase (HMGCR), which is the rate-limiting enzyme in the melavonate pathway; a pathway producing a range of cell signalling molecules with the potential to regulate oncogenesis. This is supported by strong laboratory evidence that statins induce anticarcinogenic effects on cell proliferation and survival in various cell lines [1][2][3][4] , and reduce tumour growth in a range of in vivo models [5][6][7][8][9][10] .…”
mentioning
confidence: 83%
“…These data strongly suggest that in our experimental nude mouse model, the atorvastatin-induced control of subcutaneous melanoma growth is dependent on NK cell activity. Moreover, previous studies of the anti-inflammatory effects of atorvastatin [23,24] suggest that in our experiments the atorvastatininduced increase in activated (CD69 + ) NK cells is not linked to a direct effect of atorvastatin on NK cells but is more likely due to atorvastatininduced MICA overexpression in melanoma cells. However, intraperitoneal statin injections induce systemic disruptions, which could also interfere with the innate anti-melanoma immune response by acting on Tγδ cells.…”
Section: Discussionmentioning
confidence: 70%
“…Our previous papers have shown that inhibition of RhoA/ROCK activity favors anti-melanoma immune response through MHC-class I, costimulatory molecules and FasL overexpression on melanoma cells membrane [3][4][5]. Furthermore, as previously described, the inhibition of ROCK activity reduces melanoma cells migration, invasion and metastases [23][24][25][26][27]. Consequently Atorvastatin pre-treatment of WM-266-4 cells at 1 μM mainly reduces local tumor growth and metastasis development through MICA overexpression and NK cell activity.…”
Section: Discussionmentioning
confidence: 98%